An Investigation into Valuation Inspection Templates amongst Estate Surveyors and Valuers in Nigeria - Onyejiaka, J. C.; Uzor, S. O.; Anyigor, C. K. (International Journal of Real Estate, 2025)
This study investigated valuation inspection templates amongst Estate Surveyors and Valuers in Nigeria. The research aims to determine the extent to which Estate Surveyors and Valuers use standard valuation inspection template and to identify the challenges associated. The study utilized a mixed-methods research design, combining both qualitative and quantitative approaches. A total of 260 Estate Surveyors and Valuers respondents were surveyed using a structured questionnaire. The study uncovered the level of adoption Estate Surveyors and Valuers have on the use of standard valuation inspection template in Nigeria. They should follow international standard and local code of ethics. However, the study tried identifying whether there are adequate regulatory frameworks to ensure compliance with the set minimum standard. The research identified that due to the differing nature of properties, firms produce in-house and ad-hoc template to forester practice flexibility, also the study strived to reveal any lacuna and discrepancies in this regard as it relates with the need for Estate Surveyors and Valuers to adopt global best practices to forester credibility of the process and improve the valuation procedure in general and the need for improvement. The research recommends regulatory harmonization, and technology adoption to enhance capacity building and training of Estate Surveyors and Valuers in inspection in general.